As-Ni-Co-U-Bi mineralization in Carrizal uranium ore deposit, San Juan Province. Argentina - Morello, O. (1997)
Drill samples from the Carrizal uranium ore deposit located in Western Precordillera, Province of San Juan, Argentina, were studied by petrography, ore microscopy, X-ray diffraction, energy dispersive electron microscope and microprobe methods. A mesothermal ore paragenesis composed of arsenic-nickel-cobalt-uranium-bismuth minerals was identified. The established paragenetic sequence is pyrite-bismuthinite; nickeline-gersdorffite-rammelsbergite-pechblende, in an assemblage hosted by lithic breccia. A second mineralization stage produced a porphyry copper deposit, spatially but not genetically associated with the above described assemblage. © 1997 Asociación Geológica Argentina.